제1형 자가면역성 췌장염에 동반된 진행성 위암 양상의 면역글로불린 G4 연관 위궤양 - 박정하; Joung Ha Park; 노진희; Jin Hee Noh; 이장호; Jang Ho Lee; 이고은; Goeun Lee; 홍승모; Seung-mo Hong; 조광범; Kwang Bum Cho; et al. (The Korean journal of medicine, 2019)
제1형 자가면역성 췌장염은 그 보고 빈도가 국내에서 점차 증가하는 추세이며 췌장에 국한된 질환이라기보다는 IgG4 연관 질환의 일환으로 이해되고 있다. IgG4 연관 질환은 췌장 외에도 담관, 침샘, 콩팥, 후복막 등의 다양한 장기를 침범할 수 있다. 저자들은 자가면역성 췌장염 환자에서 동반된 악성 위궤양 모양의 위 병변을 IgG4 연관 질환의 임상상으로 진단하고 스테로이드 치료 후 췌장과 위 병변 모두 호전된 증례를 경험하였기에 문헌고찰과 함께 보고하는 바이다. Type I autoimmune pancreatitis (AIP), a form of chronic pancreatitis, is included within the spectrum of immunoglobulin G4-related diseases (IgG4-RD). IgG4-RD can involve the salivary glands, bile ducts, kidneys and retroperitoneum, and the pancreas, and responds well to corticosteroid treatment. However, gastric involvement in IgG4-RD has been rarely reported. Here we report the case of a 56-year-old man with type I autoimmune pancreatitis who presented with a giant gastric ulcer mimicking advanced gastric cancer, which was subsequently determined to be IgG4-RD. Both the patient’s symptoms and his ulcerative lesions in the stomach responded to steroid treatment, which obviated the need for major surgery such as gastrectomy. Our case demonstrates the importance of recognizing potential gastric involvement in IgG4-RD, especially in a patient with concurrent AIP/IgG4-RD or a history of the disease, who is evaluated for an intractable and/or atypical gastric ulcer. A prompt diagnosis and proper management will avoid unnecessary surgery. (Korean J Med 2019;94:287-293)